Survey on sexual maturation on freshmen at the University of North Sumatera, Medan - Helena Siregar; Rusdijas Rusdidjas; A. H. Sutanto; Zakaria Siregar; M. Sjabaroedin Loebis (Indonesian Pediatric Society, 1981)
A survey was conducted on freshmen in the year 1975. They consisted of 971 students: 705 boys and 266 girls. The boy’s age ranged from18 to 23 years while the girl's age ranged from 18 to 22 years. The survey was done with the retrospective method by filiing questionnaires.We found that puberty started earlier among the girls than the boys and that menarche started at the age of 14.75 years, which was later than found in other countries.